Kinematografia na śmietniku - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This essay and review article provides a panorama of phenomena and themes related to the fundamental difference of interests and the permanent conflict stemming from the schism and crisis in values that occurs between he changes in the field of broadcasting technology and technological revolutions and the memory of cinematography and film culture.